An experimental study of corrosion damage distribution of steel bars in reinforced concrete using acoustic emission technique. (10th September 2020) - Yu, Ai-Ping; Naqvi, Mohammad Wasif; Hu, Liang-Bo; Zhao, Yan-Lin
Highlights: Acoustic Emission technique was employed in a series of controlled, accelerated corrosion tests. A Gaussian distribution function describes AE energy distribution reasonably well. Distribution of measured AE energy indicates the progression of corrosion damage and is consistent with visual evidences. A mathematical model is proposed for corrosion damage based on normalized AE energy distribution. Abstract: Corrosion of steel reinforcement usually causes damage and deterioration of the reinforced concrete. Conventional corrosion experiments or analysis typically focus on the overall corrosion of the entire reinforcing steel bar while the distribution of the corrosion along the rebar has not yet been extensively investigated. In the present study the distribution of corrosive damage was investigated in a series of controlled, accelerated corrosion tests. The acoustic emission (AE) technique was employed to correlate the acoustic emission characteristics to the corrosion along the corroded rebar. A model for the corrosion damage distribution is established based on a Gaussian distribution function. The numerical modeling results match reasonably well with experimental results in almost all corrosion tests.